Farmer business schools in Bohol, the Philippines: A gender assessment. - Kawarazuka, Nozomi; Teruel, R.T.; Babilonia, G. (International Potato Center, 2019)
This report evaluates Farmer Business Schools (FBS) from gender and social perspectives to understand how women and men involved in and benefited from FBS. The report is based on fieldwork conducted in May 2019. The authors conducted participatory film making, focus group discussions, and in‐depth interviews with three out of six FBS groups. All three FBS groups selected sweetpotato products for sale in the local markets. Complementary technical training on cooking, processing and packaging was provided in 2018.